Is Activity-Based Management Still Relevant? A Systematic Literature Review of Its Survival in the Era of Digital Disruption - Naghmantun Fadhilah; Jasmin Saidina; Nayla Syakirah Riyanti; Rifani Akbar Sulbahri (Yayasan Pendidikan Belajar Berdikari, 2026)
Relevance of Activity-Based Management (ABM) amid accelerating digital disruption remains contested. This study aims to map the development trends of ABM, analyze factors influencing its sustainability, and identify integration patterns with digital technologies through a Systematic Literature Review (SLR) approach guided by the PRISMA protocol. A total of 309 articles were identified from Scopus, Web of Science, Google Scholar, and Science Direct, with 10 articles ultimately meeting the inclusion criteria for analysis. Grounded in Contingency Theory, findings reveal that ABM has not declined in relevance but continues to evolve adaptively alongside digital transformation. Key factors sustaining ABM adoption include technological complexity, environmental sustainability demands, shifting managerial accountant competencies, and the effectiveness of digital accounting systems. Furthermore, integration of ABM with artificial intelligence, big data analytics, and cognitive time-driven costing has opened new dimensions in cost management. This study concludes that ABM remains a strategically relevant framework, provided organizations proactively integrate it with digital capabilities to maximize its managerial value. Practically, organizations adopting ABM are advised to invest in digital infrastructure particularly AI-driven cost systems and ERP platforms to enhance real-time activity tracking, improve cost accuracy, and support more responsive strategic decision-making. These practical implications suggest that ABM adoption should be accompanied by organizational readiness in terms of digital competency, system integration, and managerial commitment to continuous adaptation.